Novel rare mutation in a conserved site of PTPRB causes human hypoplastic left heart syndrome. Issue 1 (12th October 2022) - Jia, Yangying; Chen, Jianhai; Zhong, Jie; He, Xuefei; Zeng, Li; Wang, Yanmin; Li, Jiakun; Xia, Shengqian; Ye, Erdengqieqieke; Zhao, Jing; Ke, Bin; Li, Chunyu
Abstract: Hypoplastic left heart syndrome (HLHS) is a rare but fatal birth defect in which the left side of the heart is underdeveloped. HLHS accounts for 2% to 4% of congenital heart anomalies. Whole genome sequencing (WGS) was conducted for a family trio consisting of a proband and his parents. A homozygous rare variant was detected in the PTPRB (Protein Tyrosine Phosphatase Receptor Type B) gene of the proband by functional annotation and co‐segregation analysis. Sanger sequencing was used to confirm genotypes of the variant. The in silico prediction tools, including Mutation Taster, SpliceAI, and CADD, were used to predict the impact of the mutation. The allele frequencies across populations were compared based on multiple databases, including "1000 genomes" and "gnomAD". We used two vectors (pcMINI and pcDNA3.1) to generate a minigene construct to validate the mutational effect at the transcriptional level. Family‐based WGS analyses showed that only a homozygous splice acceptor variant (NC_000012.12: g.70636068T>G, NM_001109754.4: c.56‐2A>C, NG_029940.2: g.6373A>C) at the exon‐intron border of PTPRB gene associates with HLHS. This variant is also within the region with the enhancer activity based on UCSC genome annotation. Genotyping and Sanger sequencing revealed that the proband's parents are heterozygous for this variant. Evolutionary conservation analysis revealed that the site (NC_000012.12: g.70636068) is extremely conserved across species, supporting the evolutionary functional constraints of the ancestral wild type (T). In silico tools universally predicted a deleterious or disease‐causing impact of the mutation from T to G. The mutation was not found in the 1000 genomes and gnomAD databases, which indicates that this mutation is very rare in most human populations. A splicing assay indicated that the mutated minigene caused aberrant splicing of mRNA, in which a 3 bp missing in the second exon resulted in the deletion of one amino acid (NP_001103224.1:p.Glu19del) compared to the normal protein of PRPTB (also the VE‐PTP). Structure prediction revealed that the deletion occurred within the C‐region of the signal peptide of VE‐PTP, suggesting signal peptide‐related defects as a potential mechanism for the HLHS cellular pathogeny. We report a rare homozygous variant with splicing error in PTPRB associated with HLHS. Previous model species studies revealed conserved functions of PTPRB in cardiovascular and heart development in mice and zebrafish. Our study is the first report to show the association between PTPRB and HLHS in humans. Abstract : (a) The family pedigree and the sequenced samples. Previously deceased four fetuses were also indicated. (b) The color doppler ultrasound images for the fetus at 22 weeks of the mother's pregnancy indicating that the heart defects are most likely attributable to HLHS. (c) Sequencing depth and coverage summary for three individuals.